PENDIDIKAN BERKUALITAS: MENCIPTAKAN HUBUNGAN PERTEMANAN YANG SEHAT DI KALANGAN SISWA DALAM MENGURANGI BULLYING DI LINGKUNGAN SEKOLAH - Riri Herawati Prasojo; Uswatun Hasanah; Maya Oktaviani (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2024)
To improve the quality of Human Resources, it is necessary to improve the quality of education. In this case, the quality of education in Indonesia is expected to be able to bring progress to a nation and state. To overcome this, the Sustainable Development Goals (SDGs) program was enacted. One of the indicators of the implementation of the 4th SDGs is